PENGARUH WORK PASSION TERHADAP KETERLIBATAN KERJA KARYAWAN GEN Z DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA MAHASISWA PEKERJA COFFEE SHOP DI PONTIANAK) - Florentina; Alberd (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the influence of work passion on work engagement with job satisfaction as a mediating variable in Generation Z employees who work in coffee shops in Pontianak. This study uses a quantitative approach and purposive sampling techniques in sampling. A total of 160 respondents were sampled in this study, consisting of Generation Z employees aged 18–28 years, with the status of students, and working in coffee shops in Pontianak City. Questionnaires were used to collect data and Structural Equation Modeling based Partial Least Squares (SEM-PLS) was used for analysis with the help of the WarpPLS 8.0 test tool. The findings revealed show that work passioni has a positive and significant influence on work engagement and job satisfaction. Job satisfaction has a positive and significant influence on work engagement. In addition, job satisfaction is able to mediate the correlation between work passion and work involvement significantly.